Evaluation of the fracture resistance of three different core materials used for Nayyar dowel-core technique in restoring endodontically treated teeth: An in vitro study - Kakollu Sudha; Thota Murali Mohan; Bhupathi Sravanthi Yadav; Ediga Sandhya Rani; Kalagotla Aparna; Kasireddy Jyothsna (Wolters Kluwer Medknow Publications, 2020)
Background: Endodontically treated teeth have increased susceptibility to fracture. To promote the fracture resistance, reinforcing the endodontically treated teeth is of utmost importance. An ideal restoration or core is necessary to build up the coronal portion of the tooth to an ideal anatomic form before the full coverage placement. Aims: Compare the fracture resistance of Nayyar Cores of amalgam, Zirconomer, and Para Core with natural teeth . Methods: This study compared the fracture resistance of coronal-radicular restorations made from three different restorative materials. Sixty human mandibular molars were selected, 45 of which were decoronated and root treated - 15 of these molars restored with amalgam, 15 with Zirconomer, and 15 using Para Core. The 15 natural teeth used as a control group. All the teeth were mounted in acrylic and subjected to compressive loading to failure on a universal testing machine. The force required to fracture each core specimen was recorded. Results: The data of the study were statistically analyzed by ANOVA test and Tukey post hoc test. The results of the study showed that natural teeth as having the highest fracture resistance values, followed by Para Core, amalgam, and Zirconomer. The differences among all groups were significant. Conclusion: Within the limitations of this study, natural teeth showed higher fracture resistance to that of the Para Core, amalgam, and Zirconomer. Among the 3 Nayyar cores, Para Core has higher fracture resistance.